2023
DOI: 10.3390/electronics12071718
|View full text |Cite
|
Sign up to set email alerts
|

Digitalisation and Economic Growth in the European Union

Abstract: The aim of the present paper is to analyse the effects of digitalisation on economic growth in the European Union. An econometric model with balanced panel data is used, with the analysis spanning over a 22-year time frame from 2000 to 2021. The main conclusion is that digitalisation generates a positive and significant impact on economic growth, even when several control variables are taken into consideration. The results prove their robustness, which is backed by the employment of the DESI as an independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The results confirm the robustness of the relationship, which is supported by the use of DESI as an independent variable. The results of a study examining GDP output show that using DESI as an independent variable confirms the conclusion that digitalization positively influences economic growth [37]. The results of model studies showed that digitalization in the member states of the European Union has a positive effect [53][54][55][56][57] on competition, productivity, and output.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The results confirm the robustness of the relationship, which is supported by the use of DESI as an independent variable. The results of a study examining GDP output show that using DESI as an independent variable confirms the conclusion that digitalization positively influences economic growth [37]. The results of model studies showed that digitalization in the member states of the European Union has a positive effect [53][54][55][56][57] on competition, productivity, and output.…”
Section: Discussionmentioning
confidence: 62%
“…The correlation between DESI and GDP was confirmed by a study examining the situation of digital businesses in Central and Eastern Europe [36]. One study used DESI as an independent variable [37]. The study concludes that digitization positively and significantly affects economic growth, even if several control variables are considered.…”
Section: Literature Reviewmentioning
confidence: 83%
“…The dimensions are logically linked and cannot be separated, but their methodological separation allows the complex social phenomenon of digitalization to be studied. The studies analyzing the digital transformation of national economies also examine these four indicators and the changes in their values [44][45][46][47].…”
Section: Desi Of Digital Literacymentioning
confidence: 99%
“…This study examines the evolution of the DESI indicator and GDP per capita from 2015 to 2021, based on the average values of the European Union and Hungary (Table 3). The studies analyzing the digital transformation of national economies also examine these four indicators and the changes in their values [44][45][46][47].…”
Section: The State Of Digital Transformation In Hungary Based On Desi...mentioning
confidence: 99%
“…The recognition of digitalization as a crucial element in tackling pollution has been growing, with researchers and policymakers extensively reviewing its external impact on environmental sustainability (Lee et al, 2023). In their research, Mura and Donath (2023) suggested a positive link between digitalization and economic growth, highlighting the potential for significant contributions toward establishing a sustainable environment. Likewise, Nazari and Musilek (2023) emphasized the anticipated improvements in global energy systems by integrating digital technologies, enhancing reliability, innovation, and sustainability.…”
Section: Introductionmentioning
confidence: 99%